(untitled) (Estudos em Design, 2024)
Editores Cristina Portugal Rita Couto Avaliadores desta edição v. 32, n. 2 (2024) Adriana Gralow Adriana Miranda Adriana Sampaio Leite Alexandre Oliveira Aline Savi Álvaro Sousa Ana Beatriz Pereira de Andrade Ana Berwanger Ana Pazmino André Ribeiro de Oliveira Andréa Almeida Andréa Silva Angelica Adverse Antonio Colchete Filho Beany Monteiro Carlo Franzato Cassia Carrara Domiciano Cayley Guimaraes Cláudia Silva Cristiane Aun Bertoldi Chrystianne Ivanóski Cyntia Malaguti de Sousa Daniel Portugal Daniel Raposo Daniela Estaregue Alves Debora Buonano Deborah Christo Doris Kosminsky Edson Rufino Eloiza Corrêa da Silva Everton da Silva Frederico Braida Gabriel Patrocinio Gabriela Perry Gisele Saraiva Joana Contino Karina Porto Bontempo Laura Martins Letícia Fonseca Livia Flavia Campos Luiza Falcão Soares Cunha Madalena Grimaldi Marcio Guimarães Marcos Braga Marilda Lopes Pinheiro Queluz Maria Teresa Lopes Marina Kunst Mariano Lopes de Andrade Neto Maurício Klafke Dick Rafaella Peres Raimundo Diniz Ravi Passos Renata Cadena Renata Wanderley Rogério Camara Rosiane Pereira Alves Sandra Maria Souza Sérgio Luciano da Silva Tiago Silva Vagner Godói Wagner Bandeira Walter Neto Viviane Nunes